A revised classification of the family Dasyatidae (Chondrichthyes: Myliobatiformes) based on new morphological and molecular insights - Last, Peter R.; Naylor, Gavin J.p.; Manjaji-Matsumoto, B. Mabel (Zootaxa, 2016)
The higher-level taxonomy of the stingrays (Dasyatidae) has never been comprehensively reviewed. Recent phylogenetic studies, supported by morphological data, have provided evidence that the group is monophyletic and consists of four major subgroups, the subfamilies Dasyatinae, Neotrygoninae, Urogymninae and Hypolophinae. A morphologically based review of 89 currently recognised species, undertaken for a guide to the world’s rays, indicated that most of the currently recognised dasyatid genera are not monophyletic groups. These findings were supported by molecular analyses using the NADH2 gene for about 77 of these species, and this topology is supported by preliminary analyses base on whole mitochondrial genome comparisons. These molecular analyses, based on data generated from the Chondrichthyan Tree of Life project, are the most taxon-rich data available for this family. Material from all of the presently recognised genera (Dasyatis, Pteroplatytrygon and Taeniurops [Dasyatinae]; Neotrygon and Taeniura [Neotrygoninae]; Himantura and Urogymnus [Urogymninae]; and Makararaja and Pastinachus [Hypolophinae]), are included and their validity largely supported. Urogymnus and the two most species rich genera, Dasyatis and Himantura, are not considered to be monophyletic and were redefined based on external morphology. Seven new genus-level taxa are erected (Megatrygon and Telatrygon [Dasyatinae]; Brevitrygon, Fluvitrygon, Fontitrygon, Maculabatis and Pateobatis [Urogymninae], and an additional three (Bathytoshia, Hemitrygon and Hypanus [Dasyatinae]) are resurrected from the synonymy of Dasyatis. The monotypic genus Megatrygon clustered with ‘amphi-American Himantura’ outside the Dasyatidae, and instead as the sister group of the Potamotrygonidae and Urotrygonidae. Megatrygon is provisionally retained in the Dasyatinae pending further investigation of its internal anatomy. The morphologically divergent groups, Bathytoshia and Pteroplatytrygon, possibly form a single monophyletic group so further investigation is needed to confirm the validity of Pteroplatytrygon. A reclassification of the family Dasyatidae is provided and the above taxa are defined based on new morphological data.